2024
DOI: 10.3390/su16030978
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ AI-TPACK: Exploring the Relationship between Knowledge Elements

Yimin Ning,
Cheng Zhang,
Binyan Xu
et al.

Abstract: The profound impact of artificial intelligence (AI) on the modes of teaching and learning necessitates a reexamination of the interrelationships among technology, pedagogy, and subject matter. Given this context, we endeavor to construct a framework for integrating the Technological Pedagogical Content Knowledge of Artificial Intelligence Technology (Artificial Intelligence—Technological Pedagogical Content Knowledge, AI-TPACK) aimed at elucidating the complex interrelations and synergistic effects of AI techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 97 publications
(115 reference statements)
0
1
1
Order By: Relevance
“…If content knowledge is used to use its PCK and TCK capabilities, then it will impact TPACK. These findings contrast significantly, ly from those of a study by (Ning et al, 2024)which found that teacher TPACK is impacted both directly and indirectly by the CK, PK, and PCK components.…”
Section: Examining Variant Test Of Determination Analysiscontrasting
confidence: 91%
“…If content knowledge is used to use its PCK and TCK capabilities, then it will impact TPACK. These findings contrast significantly, ly from those of a study by (Ning et al, 2024)which found that teacher TPACK is impacted both directly and indirectly by the CK, PK, and PCK components.…”
Section: Examining Variant Test Of Determination Analysiscontrasting
confidence: 91%
“…This is supported by previous studies, indicating that a profound understanding of education for sustainability, coupled with ICT tools underpinned by transformative teaching and learning, bolsters the creation of contextualized curricula and enriches the teaching and learning experience [75,76], especially through multidisciplinary projects [77]. These results also suggest the need to cultivate teachers' digital competence that reflects the Technological Pedagogical Content Knowledge (TPACK) methodology [78], especially taking into consideration the synergistic effects of recent advances in AI technology, supported by innovative pedagogical methods, and contextualized with multiple subject-specific content in the broader field of education; this is termed AI-TPACK [79].…”
Section: Discussionmentioning
confidence: 98%